Analisis Agradasi, Degradasi dan Sedimentasi di Sungai Pabelan Pasca Erupsi Gunung Merapi 2010 - Zeolita Aprilian; Dhemi Harlan; Edy Anto Soentoro; Aulia Zahroni (Journal on Education, 2023)
Mount Merapi is the most active volcano in Indonesia, the eruption that occurred in 2010 was a major eruption with a recurrence of once every 100 years. Of the 140 million m3 of potential cold lava of Mount Merapi, 24 million m3 of them flow into the Pabelan River. One of the disaster mitigation on the Pabelan River is the Sabo Dam infrastructure, currently on the Pabelan River there are 23 Sabo Dams, in 2022 an additional 1 Sabo Dam has been built, namely PAC-Menayu. In this study, modeling will be carried out using 1D Kanako before the construction of 1 Sabo Dam and after the construction of 1 Sabo Dam with river geometry from 2020 measurements and flood discharge generated from rainfall triggering debris flow on February 03, 2011 at the Jrakah Rain Post, from this rainfall a 6-hour rain distribution was carried out using the PSA coefficient to be inputted in HEC-HMS. From the results of Kanako modeling, it is concluded that the construction of the new Sabo Dam is able to reduce sedimentation by 52.88 m3 and it is obtained that the construction of 24 Sabo Dams is effective in containing sediment by 32.6% of the total potential for cold lava of 24,000,000 m3 flowing in the Pabelan River so that it is appropriate as a disaster mitigation effort, namely reducing the potential for debris flooding in the future